2014
DOI: 10.6090/jarq.48.355
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Extraction of Low-molecular-weight Phenolic Compounds from Oil Palm Biomass

Abstract: Subcritical water extraction of low-molecular-weight phenolic compounds from oil palm biomass (trunk, bark, petiole, rachis, leaves, empty fruit bunch fiber, midrib spine leaflets, stalk of fruit bunches, flesh, kernel shells, and albumen) was conducted. It was elucidated that gallic acid, protocatechuicaldehyde, p-hydroxybenzoic acid, p-hydroxybenzaldehyde, vanillic acid, syringic acid, vanillin, syringaldehyde p-coumaric acid and ferulic acid, all of which could be used as 2-pyrone-4,6-dicarboxylic acid (PDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Finding renewable sources of this phenolic compound is an interesting alternative towards a more sustainable economy. Kawamura et al ( 37 ) proposed that low-molecular-mass phenolic compounds could be used for the production of 2-pyrone-4,6-dicarboxylic acid, which is a precursor for the production of various polymers such as polyamide, polyester and polyurethane.…”
Section: Resultsmentioning
confidence: 99%
“…Finding renewable sources of this phenolic compound is an interesting alternative towards a more sustainable economy. Kawamura et al ( 37 ) proposed that low-molecular-mass phenolic compounds could be used for the production of 2-pyrone-4,6-dicarboxylic acid, which is a precursor for the production of various polymers such as polyamide, polyester and polyurethane.…”
Section: Resultsmentioning
confidence: 99%
“…However, the percent recovery of coumarin decreased to 91% and 82% at 200 • C and 250 • C, respectively, after heating for 60 min, as shown in Table 2. This means that there is a minor degradation of coumarin at 200 • C and 250 • C. Although Kawamura et al did not extract coumarin in their work, they did report that the subcritical water extraction yield for p-coumaric acid reached a maximum at 160 • C and then decreased at 180 • C and 200 • C [32]. This result suggests that p-coumaric acid may be degraded at temperatures higher than 160 • C. This is in agreement with our findings for coumarin's stability in subcritical water.…”
Section: Stability Of Vanillin and Coumarin In Subcritical Watermentioning
confidence: 95%
“…Thus, no significant degradation of vanillin occurred under the subcritical water conditions investigated. Kawamura et al reported that the subcritical water extraction yield for vanillin from oil palm trunk continued to increase between 100 • C to 200 • C [32]. This may suggest that no degradation of vanillin occurs, and the compound is stable in water at temperatures up to 200 • C during the process of subcritical water extraction.…”
Section: Stability Of Vanillin and Coumarin In Subcritical Watermentioning
confidence: 99%
“…Some of these compounds are produced as secondary metabolites in plants. 4-HBA and 3,4-dihydroxy-benzaldehyde (DHBA) are present in Origanum vulgare L. [18], oil palm biomass [19], Potentilla fulgens [20], sugarcane molasses [21] and vanilla pods [22]. 4-HBA and 4-AP are present in Dilobeia thouarsii [23].…”
Section: Introductionmentioning
confidence: 99%